Equity Home Bias, Financial Integration, and Regulatory Reforms: Implications for Emerging Asia - Cyn-Young Park; Rogelio V. Mercado (Asian Development Bank (ADB), 2014)
With increasing financial integration and improving regulatory quality, we expect equity home bias to decline. Drawing on the supportive evidence for such trends in advanced economies, this paper investigates the links between financial integration and regulatory quality; and equity home bias in emerging Asia. To test the significance, a pooled OLS estimation was used. The results show that greater global and regional financial integration and better regulatory quality significantly lower equity home bias against global and regional stocks. The estimates also find that the lag value of the home bias significantly lowers equity home bias against global and regional equities; while bank assets and stock market capitalization increase the said bias against global and regional equities. Interestingly, volatility of foreign exchange rate significantly increases equity home bias against regional stocks, but not for the home bias against global stocks. The results suggest that if ongoing financial regulatory reforms lead to less information asymmetry and lower transaction and information costs in emerging Asia, equity home bias will continue to decline, allowing for greater portfolio diversification and more efficient allocation of capital resources.
hdl:11540/1293
Keywords: F36; G11; G28; 330; equity home bias; financial integration; regulatory reforms